2015
DOI: 10.15356/0373-2444-2013-2-104-114
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Altitude Area of Nordmann fi r in the Western Caucasus (Basin of Belaya River) in the Relation with the Global Warming Issue

Abstract: Поступила в редакцию 27.03.2012 г.На основе анализа возрастной структуры популяций определена тенденция изменения верхней и нижней границ распространения пихты Нордмана (Abies nordmanniana) в бассейне реки Белая (Западный Кавказ) в связи с потеплением климата. Результаты свидетельствуют, что климатические перемены пока не привели к изменению высотного ареала этого вида в районе исследований, но создали предпосылки к его отступлению на верхних и нижних пределах.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Previous research also revealed a high sensitivity to climate humidity of Abies nordmanniana in the Caucasus (Litvinskaya and Salina 2012) and Picea orientalis in Turkey (Ucarcı and Bilir 2018). According to Akatov et al (2013), the suitable average annual precipitation for Abies nordmanniana ranged from 700 to 2500 mm. Our result is also consistent with a previous study of r forests in northwestern Turkey (Coban 2020), which showed that pure r forests mainly occurred between 1000 and 1600 m above sea level on mountain slopes with a steepness of about 10-20°.…”
Section: A Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research also revealed a high sensitivity to climate humidity of Abies nordmanniana in the Caucasus (Litvinskaya and Salina 2012) and Picea orientalis in Turkey (Ucarcı and Bilir 2018). According to Akatov et al (2013), the suitable average annual precipitation for Abies nordmanniana ranged from 700 to 2500 mm. Our result is also consistent with a previous study of r forests in northwestern Turkey (Coban 2020), which showed that pure r forests mainly occurred between 1000 and 1600 m above sea level on mountain slopes with a steepness of about 10-20°.…”
Section: A Modelmentioning
confidence: 99%
“…Fir forests of Abies nordmanniana concentrate in the mountains of the Western Greater Caucasus (Litvinskaya and Salina 2012). In this area, r forests were prone to deforestation, bacterial diseases, and the negative impact of climate change (Akatov et al 2013;Bebiya 2015;Gornov et al 2018). The entire native range of Abies nordmanniana encompasses the Russian Caucasus, Georgia, and the northeastern Turkey.…”
mentioning
confidence: 99%
“…Studies of Caucasian populations of Abies nordmanniana are concentrated in the Western Caucasus, where the main fir forests are located. The main territories are the basins of the Pshekh, Belaya, Laba rivers on the northern macroslope of the Greater Caucasus and the upper reaches of the Mzymta, Psou, Bzych, Rioni rivers on the southern macroslope [23,24]. The researchers noted the vulnerability of the Caucasus fir forests as a result of the negative anthropogenic (deforestation), climatic and biotic (mass bacterial diseases) impacts [24,25].…”
Section: Studied Speciesmentioning
confidence: 99%
“…The main territories are the basins of the Pshekh, Belaya, Laba rivers on the northern macroslope of the Greater Caucasus and the upper reaches of the Mzymta, Psou, Bzych, Rioni rivers on the southern macroslope [23,24]. The researchers noted the vulnerability of the Caucasus fir forests as a result of the negative anthropogenic (deforestation), climatic and biotic (mass bacterial diseases) impacts [24,25]. At the same time, the main research fields of the last two decades were dendrochronology [26], the climate-driven changes in the altitude boundaries of the species [24], forest restoration [27], mapping of dark coniferous forests with Abies nordmanniana [28,29].…”
Section: Studied Speciesmentioning
confidence: 99%
See 1 more Smart Citation